Collaboration Between Family and Healthcare Providers in the Management of Abortus Imminens: A Case Study from Jonggat District, Central Lombok (Journal of Social And Education Research, 2025)
Abortus imminens is a high-risk pregnancy condition that requires prompt management to maintain the pregnancy and prevent serious complications such as miscarriage. This study aims to analyze the assessment, diagnosis, intervention, and evaluation processes in midwifery care for a case of abortus imminens in Dusun Makam, Desa Jelantik, Kecamatan Jonggat, Kabupaten Lombok Tengah. Data were collected in a focused manner through direct approaches by a midwifery professional student, with the support of the patient, family, and local healthcare providers. The diagnosis was established based on subjective data, objective findings, and supporting examinations in accordance with midwifery theory. The main intervention involved education about the importance of bed rest and effective communication (KIE), carried out collaboratively with the patient and other healthcare personnel. Evaluation showed improvement in the pregnancy condition after the intervention. This study highlights the importance of accurate assessment, early intervention, and multidisciplinary cooperation in improving midwifery care outcomes for abortus imminens cases.